Nation-based peer assessment of Europe's Sustainable Development Goal performance. - Enda Murphy; Patrick Paul Walsh; Ethan Murphy (PLoS ONE)
Less than seven years remain for Europe to meet the targets of the United Nations Sustainable Development Goals (SDGs). However robust and accurate methods for assessing SDG progress are currently lacking. Through the development of several SDG indices, this study addresses this critical knowledge gap by providing the means to accurately identify national 'problem areas' and thereby accelerate SDG achievement. Specifically, an indicator-based approach has been used to create a composite index containing 166 unique SDG indicators that assess a nation's SDG performance compared to the best and worst performers in the European Union (EU). Our results indicate that each EU nation is on average, 58% of the way towards the best performer in the overall SDG indicator framework. A nuanced taxonomy has been developed that allows for the assessment of SDG performance in several critical dimensions of the SDGs, including in 'Means-of-Implementation (MoI)', 'Linkage', and 'Outcome' indicators. The index's comprehensive framework allows for EU's performance in individual SDG indicators to be investigated while providing the most accurate assessment of national SDG performance, to date. Overall, the indices presented in this paper can significantly enhance the understanding of SDG performance while concurrently guiding national and EU SDG policy development.